Tropical upper tropospheric ozone enhancements due to potential vorticity intrusions over Indian sector. (September 2015) - Sandhya, M.; Sridharan, S.; Indira Devi, M.; Gadhavi, H.
Abstract: Influence of potential vorticity (PV) intrusions at 13.5°N over and near Indian sector (50°E–90°E) on tropical upper tropospheric ozone mixing ratio (OMR) variations is demonstrated based on two case studies. Increase of ECMWF (European Centre for Medium-range Weather Forecasting) reanalysis (ERA)-interim OMR in the upper troposphere (200–500 hPa) is observed during the intrusion events consistently in both cases. The OMR also shows similar tongue like structure as PV and it even follows the spatial shift of the PV tongue. In addition, the enhancements in the upper tropospheric OMR during the intrusion events are confirmed using microwave limb sounder (MLS) ozone data at 216 hPa. It is suggested that the existence of strong downdrafts, associated with the ageostrophic circulation due to jet stream, which is inferred from longitude-height cross-section of ERA-interim vertical velocity could bring the ozone further down, though high PV tongue remains only at higher level (above 400 hPa). The importance of these results lies in demonstrating the role of PV intrusion events on the enhancement of tropical upper tropospheric ozone over Indian sector, where the impact of the PV intrusions is not well understood when compared to that over Pacific and Atlantic sectors. Highlights: Ozone enhancement in the tropical upper troposphere due to PV intrusion events. Ozone follows both structure and spatial shift of the PV intrusions. Downdrafts due to ageostropic circulation transports ozone to lower heights.